Social Representations and Anchorages of Childhood Depression (Research, Society and Development, 2022)
This study aims to analyze the social representations (RS) of childhood depression. This is a quanti-qualitative study, anchored to the theoretical contribution of the Theory of Social Representations (RS). The study included 120 children, aged between 8 and 12 years (M = 2.0; SD = 0.47), from the city of Campina Grande-PB, in the school context and who mostly lives with their parents (83.3%). The data came from the Free Association of Words Technique (TALP) in the face of stimuli; depression, depressed person and myself. These stimuli were processed by the Tri-Deux-Mots software and analyzed through a Correspondence Factor Analysis (CFA). The results show that depression, depressed person and children’s self-perception about depression are represented in a multifaceted way from the different anchorages. Specifically, it appears that the representations of social actors about depression are anchored in feelings of fragility, suicide, discouragement, which corroborates to an elaborate knowledge and shared socially.The data of this research point to the construction of practical knowledge about the social representations of childhood depression contributing to the development of interventions and actions, as well as in the prevention of future cases of depression in the school context.